THE MAN CHARACTER’S PERSONALITY CHANGE AS REFLECTED IN DEFOE’S ROBINSON CRUSOE - Imam Basuki (LITERASI: Indonesian Journal of Humanities, 2012)
Robinson Crusoe is a novel written by Daniel Defoe telling about a story of Robinson Crusoe’s life experiences in the three places such as in York, at sea and in the islands. This article discusses about these places, particularly the last place, and the events experienced by Crusoe that can influence his personality change. Therefore, the qualitative research is done to know whether the setting and the events undergone by him, as the main character, can change his personality or not, by applying Murray’s theory of personality describing how personality is formed. This theory employs three sets of determinants: group membership, situational and constitutional. It is also applied the psychological approach to analyze the main character’s personality and to find out the setting and the events influencing his personality change. The result of the research proves that there has been a close relation between setting and personality in which setting and the events experienced by Crusoe during his life adventure in the three places can influence the change of his personality.Keywords: setting, life experiences, personality change